Wasatiyyah Da’wah and Religious Freedom in Malaysia: A Constitutional Perspective - Yusuf, Fakhri; Murdani, T; Fairus, Fairus; Rasyidah, Rasyidah; Jarnawi, Jarnawi; Zuhdi, Ahmad; AB, Syamsuddin (SCAD Independent, 2025)
This article examines the constitutional legitimacy and practical implications of Wasatiyyah da’wah—an Islamic propagation model rooted in the principle of moderation—in Malaysia’s plural legal and religious context. While the Federal Constitution recognizes Islam as the religion of the Federation (Article 3(1)), it also guarantees religious freedom (Article 11), creating a legal space that necessitates careful interpretation and application. This study uses a normative legal methodology to analyze constitutional texts, statutory instruments, and judicial decisions through systematic, teleological, and contextual interpretations. The findings indicate that Wasatiyyah da’wah may function as a constitutionally compatible approach to Islamic propagation, provided it avoids coercion and adheres to legal safeguards. However, tensions arise in its implementation, especially when state-sponsored religious programs intersect with public welfare, education, and minority rights. The institutionalization of Wasatiyyah must be accompanied by transparent regulation, independent oversight, and alignment with human rights principles. By treating Wasatiyyah not merely as a theological ideal but as a constitutional strategy, the study contributes to constitutional Islamic studies and offers insights into reconciling Islamic identity with democratic pluralism. The research also opens avenues for comparative studies in other Muslim-majority societies facing similar legal and social challenges.